Realita Visualitas Generasi Z dalam Mise en Scene Iklan Shopee Men Sale - Deni Kristanto; Wiwik Sushartami; Budi Irawanto (ULTIMART Jurnal Komunikasi Visual, 2022)
Massive and rapid development of Internet 2.0 in society opens up opportunities for exploitation of personal and communal life. A series of efforts by sellers of services and products on the internet are competing to be trusted by the digital community, a series of visual charms on digital screens seems to be present to describe their behavior and experiences in the real world for the sake of capital needs. As the most accessed media in Indonesia, especially Generation Z or Digital Natives, YouTube is one of the harmful media that opens up opportunities for exploitation. YouTube Shopee Men Sale ad is a case of how one of the largest online stores in Indonesia constructively approaches the most potential YouTube Generation Z user for commodity purposes. With a qualitative analysis and a Close Textual Analysis approach, this study aims to find out how the visuality patterns of YouTube ads Shopee 8.8 Men Sale 2019 and Shopee 2.2 Men Sale 2021, present the values ​​and social image of Generation Z for their commodity needs. Then through this research it is known that the two advertisements constructively through the use of visual aspects of mise en scene try to recreate reality that is related to the experiences and behavior of Generation Z. Keywords: reality; visual aspect; youtube advertising; shopee men sale; mise en scene; generation z.